Bull riding - Sherman, Josepha (Chicago, Ill. : Heinemann Library, 2000)
Explores the origins and development of bull riding as a rodeo event, discussing the rules, the training, the judging, and the animal and human stars.
8 - 12 years
Keywords: Bull riding -- Juvenile literature; Bull riding; Rodeos